Clinico-pathological and demographic profile of patients with carcinoma stomach: a tertiary care experience - Mir, Shabir Ahmad; Intikhab, Mir; Dar, Hanief Mohamed; Wani, Mumtazdin (International Surgery Journal, 2019)
Background: Gastric cancer is a common malignancy all over the world, and our valley is not an exception. Under this background, we conducted the present study at our tertiary care hospital to look into the clinico-demographic profile of this disease. Aim was to determine the clinico-pathological and demographic profile of patients with carcinoma stomach attending to our tertiary care hospital. Methods: This prospective study was conducted in unit-II of department of general surgery in Shri Maharaja Harisingh hospital Srinagar, over a period of 5.5 years from July 2012 to December 2017. All patients with histopathological diagnosis of gastric malignancy were included and analysed. Results: Male to female ratio was 1.4:1 with mean age of 63.23 years. The most common histopathological type of gastric malignancy was adenocarcinoma (85.84%) followed by lymphoma. The most common location of the gastric cancer was distal third of the stomach. Fifty-seven patients (50.4%) were offered definitive surgery and 21(18.58%) were managed by palliative surgery. Out of 113 patients, 87 patients (76.9%) had present or past history of smoking. The most common presentation in our study was dyspepsia. Conclusions: Profile of gastric carcinoma in our institution is not in wide variance with that of other studies. A significant proportion of patients presented with an advanced or unresectable disease because of the delay in proper screening. All patients with history of dyspepsia (age >50 years) and anemia should undergo screening upper gastrointestinal (UGI) endoscopy at the earliest, so that we can detect the lesion at the initial stage.